THE STUDY ON CUSTOMER BEHAVIOUR TO AVO WASHING LIQUID PRODUCT OF HASO COMPANY - Le, Ha Phuong (Tạp chí Công thương, 2019)
The study on “Customers’ behaviour to AVO washing liquid product of Hanoi soap company” aim to find the behavior, preferences and habits of consumers washing liquid in Hanoi through qualitative research and quantitative research method. The results of the analysis will be used by the company to develop appropriate marketing solutions for the product. The study used both qualitative and quantitative methods with in-deep interviews and a questionnaire to assess customers’ awareness about AVO washing liquid product of Hanoi soap company and evaluate the factors affect customer satisfaction and loyalty. There were 326 participants who are current customers and potential customers of HASO company took part in the survey.